Development by popular protection and Tunisia: the case of Tataouine. Issue 7 (10th November 2019) - Ajl, Max
ABSTRACT: Recently a debate re-emerged between Adel Samara and Samir Amin on the state role in delinking – subjecting a social formation's relationships to the world-system to a domestic, popular law of value. I suggest the arguments turns on the agent helming development. Amin's agent is slightly more ambiguous than Samara's, reflecting de-linking is modelled on postrevolutionary planning in Maoist China, with an explicit state role, whereas Samara, theorizing development under military occupation, spurned the state. The article assesses the arguments against contemporary Tunisia. It shows how flourishing Tunisian struggles track Samara's development by popular protection (DBPP). The subject of history is masses engaged in struggle with state-mediated accumulation. It focuses on Tataouine's 2017–2018 ElKamour protests. It argues Amin (1) articulates an antisystemic ideology, crucial amidst ideological disarray; (2) offers ideas for changes in financial architecture – holding programmes amidst capitalist advance; (3) build up the delinking framework which DBPP expands.